Wildfire smoke and antimicrobial resistance: A hidden link demanding global attention - Ronan Adler Tavella; Fábio Parra Sellera; Daniela Debone; Simone Georges El Khouri Miraglia; Rodrigo Cayô; Nilton Lincopan; Ana Cristina Gales; Arnaldo Lopes Colombo; Sergio Schenkman; João Pedro Rueda Furlan (Ambio, 2026)
Wildfire smoke represents an underrecognized yet potentially important contributor to the dissemination of antimicrobial resistance (AMR). As wildfires increase in frequency and intensity due to climate change, they release vast amounts of PM 2.5 , particles with the potential to transport antimicrobial-resistant microorganisms and genetic elements across long distances. These severe air pollution events create multifactorial pressures on human and environmental health: increasing antimicrobial prescriptions through respiratory and systemic illnesses, overwhelming healthcare systems, and facilitating the environmental spread of multidrug-resistant strains through deposition in water, soil, and agri-food systems. This perspective highlights how wildfire-related PM 2.5 may act as a direct vehicle and an indirect driver of AMR propagation across One Health domains. We emphasize the urgent need to integrate AMR surveillance into air quality monitoring, particularly in vulnerable regions. Understanding this possible relationship is essential for informing future research priorities, guiding public health strategies, and advancing interdisciplinary approaches to address these converging global health threats.

Brazil’s climate leadership paradox: hosting COP30 amid domestic environmental rollbacks - Daniela Debone; Ronan Adler Tavella; Mariana Vieira da Costa; Eliane Seiko Maffi Yamada; Flavio Manoel Rodrigues da Silva Júnior; Sandra de Souza Hacon; Paulo Artaxo; Simone Georges El Khouri Miraglia (International Environmental Agreements: Politics, Law and Economics, 2026)

Coarse particulate matter air pollution in Porto Metropolitan area, Portugal: time series analysis, trends and implications for public policies - Simone Georges El Khouri Miraglia; Ronan Adler Tavella; Daniela Debone; Rui Moreira Barbosa; Flavio Manoel Rodrigues da Silva Júnior; Clara Lopes Ribeiro; Simone Morais; Marisa Alexandra Marques Freitas (Environmental Science and Pollution Research, 2026)
Air pollution remains a persistent environmental and public health concern in urban regions. This study presents a 22-year analysis (2001–2022) of coarse particulate matter (PM 10 ) concentrations across 15 monitoring stations in the Porto Metropolitan Area (PMA), Portugal. The stations, pre-classified by national authorities as traffic, background-urban, background-suburban, or industrial, were used to assess long-term temporal trends and spatial variability. Annual mean PM 10 concentrations were calculated and linear regression was applied to evaluate trends. Differences between station types were tested using statistical analysis. The results revealed consistent decline in PM 10 levels from the early 2000s to the mid-2010s, followed by stagnation or increases at several stations in the final years of the series. While higher concentrations were historically observed at traffic and industrial sites, no statistically significant differences in annual mean PM 10 concentrations were found between stations of different classifications or within classifications, even when comparing distinct time periods. This homogeneity suggests widespread regional exposure, likely driven by shared emission sources, atmospheric transport, and urban development patterns across the PMA. When compared to World Health Organization (WHO) air quality guidelines, exceedances were frequent and persistent. From 2001 to 2011, nearly all stations with valid data exceeded the 2005 guideline of 20 µg/m 3 . Between 2012 and 2020, the exceedances gradually decreased, although several stations still surpassed the guideline. However, under the 2021 WHO guideline (15 µg/m 3 ), all stations with valid data for 2021 and 2022 again exceeded the guideline. These findings highlight the need for integrated, long-term air quality policies. Clinical trial number: Not applicable.

Butyl toluidine blue as a photosensitizer for antimicrobial photodynamic therapy on titanium-associated biofilms - Amanda Paino Santana; Daniela Moreira Cunha; Rodolfo Debone Piazza; Mark Wainwright; Magda Feres; Belen Retamal-Valdes; Rafael Scaf de Molon; Valdir Gouveia Garcia; Leticia Helena Theodoro; Wirley Gonçalves Assunção; Erica Dorigatti de Avila (Journal of Photochemistry and Photobiology B: Biology, 2025)

Impact of Climate Change-Mediated Tragedies: An Account of Extreme Rainfall Event in Rio Grande do Sul, Brazil - Daniela Debone; Ronan Adler Tavella; Arnaldo Lopes Colombo; Ana Cristina Gales; Flávio Manoel Rodrigues da Silva Júnior; Simone Georges El Khouri Miraglia (Anthropocene Science, 2025)

Environmental Impacts of Brazilian Beef Production and Mitigation Alternatives—A Systematized Review - Mariana Vieira da Costa; Daniela Debone; Simone Georges El Khouri Miraglia (Agricultural Research, 2025)

A population under smoke: fire events trigger severe air pollution in Portugal - Simone Georges El Khouri Miraglia; Daniela Debone; Clara Lopes Ribeiro; Rui Moreira Barbosa; Ronan Adler Tavella; Flavio Manoel Rodrigues da Silva-Júnior; Manuela Vieira da Silva; Marisa Alexandra Marques Freitas (Environmental Science and Pollution Research, 2025)

Unprecedented air quality crisis: The impact of widespread fires on air pollution in São Paulo - Simone Georges El Khouri Miraglia; Ronan Adler Tavella; Daniela Debone (Air Quality, Atmosphere & Health, 2025)

Brazilian beef production and GHG emission – social cost of carbon and perspectives for climate change mitigation - Mariana Vieira da Costa; Daniela Debone; Simone Georges El Khouri Miraglia (Environmental Science and Pollution Research, 2025)

Does air pollution explain COVID-19 fatality and mortality rates? A multi-city study in São Paulo state, Brazil - Luciana Ferreira Leite Leirião; Daniela Debone; Simone Georges El Khouri Miraglia (Environmental Monitoring and Assessment, 2022)